Fuzzy logic predictive model of tool wear in end milling glass fibre reinforced polymer composites - Azwan Iskandar, Azmi; Lin, Richard J.T.; Bhattacharyya, Debes (Trans Tech Publications., 2012)
Link to publisher's homepage at http://www.ttp.net/